Onde e como você mora: Uma análise do direito à moradia a partir das ZEIS instituídas em Montes Claros/MG para abrigar os empreendimentos imobiliários do PMCMV" - Ana Paula de Souza Reis Assis (2018)
The city, as a space built and ruled by the capitalist logic, is a stage for socio-spatial inequalities. Urban land and housing, under this rationality, are transformed into a commodity, through production of space and reproduction of capital. In these processes, there is an overlapping of the exchange value over the value of use, making this new commodity expensive and inaccessible to the low-income population. Social and structural reflection of the urban space production and the role played by its producer agents is the housing deficit, which, for this part of the population, is about 80% of the demand for housing, according to the FJP (2014) data. This reality imposes on the State the adoption of urban planning and public policies that can minimize this problem. The PMCMV is a public housing and macroeconomic policy that aims to provide access to housing for families with incomes of up to 10 minimum wages. Allied to this policy, the use of the ZEIS instrument was encouraged by the municipalities, so they could mitigate land regularization rules as well as land use and occupation to receive the projects linked to the program. It is within this context that the objective proposed by the present research to analyze the right to housing in the ZEIS established in Montes Claros, as from 2009, linked to the PMCMV, track 01, is inserted. The specific objectives are to study the planning and the urban housing policies adopted by City of Montes Claros; understand the roles of space-producing agents involved in the establishment of the ZEIS and the interests of each one of them in the process; and to diagnose the ZEIS established in Montes Claros between 2008 and 2018. For that, it has been used a methodology based on qualitative approach and bibliographic, documentary and field research - using this interview and iconographic register. It was observed that in Montes Claros, the PMCMV, quantitatively, offered access to housing to more than 4,500 low-income families, in its phases 01 and 02, implemented between the years of 2011 and 2016. The institution of empty ZEIS be the ones foreseen by the Land Use and Occupancy Law in 2009 or to host PMCMV housing developments - contributed to the urban expansion, bordering the vectors south, east, northeast, north and northwest of the city. The creation of the ZEIS consisted of a form of urban space production that exacerbated the socio-spatial segregation already existing in Montes Claros, evidencing the producing agents of space: State, real estate groups and capitalists. It is verified that the population residing in the 10 enterprises of the PMCMV track 01 do not have their right to housing observed, although they have had access to a housing unit, considering the location criteria, established by Comment nº 4 of the UN Committee on Economic, Social and Cultural Rights. By this criterion, people must have access or easy access to services such as education, health, transportation, leisure, which is not offered to the resident population. None of the 10 inhabited residential areas have school, kindergarten, health station, police station, sports court, public square, which evidences socio-spatial segregation. The access to these services and equipment is hampered by the chosen location to host the development. In this perspective, not only the right to housing is not concretized, but also the right to the city of this part of the population is denied.